Greek Deuteronomy's "Fever and Chills" and Their Magical Afterlife - Lincicum, D (2008)
The Greek text of Deut. xxviii 22 preserves the earliest reference in a Jewish context to "fever and chills", a pair that repeatedly surfaces in later incantations. This provided both a scriptural justification for some Greek curses and contributed to the "magical Wirkungsgeschichte" of Deuteronomy itself. © 2008 Brill Academic Publishers.